Analisis Akibat Hukum Pemutusan Hubungan Kerja Sepihak oleh PT. Panca Mitra Multi Perdana - Arifan Oktafianto; Eka Nur Toyyiba (Bhirawa Law Journal, 2026)
This study aims to analyze the legal consequences for workers in the Industrial Relations Court Decision Number 88/Pdt.Sus-PHI/2025/PN Sby regarding unilateral termination of employment due to rationalization carried out by PT Panca Mitra Multi Perdana. This research is motivated by the termination of employment of 17 workers without prior socialization and the non-fulfillment of wages and severance pay rights. This study uses a normative juridical method with a statutory approach and a case approach to the court decision that is the object of the study. The results show that the industrial relations dispute occurred because the company terminated employment for efficiency reasons but had not fulfilled the obligation to pay wages and workers' compensation in accordance with the provisions of Government Regulation Number 35 of 2021. In the lawsuit, the workers demanded that the employment relationship be declared terminated and the company be punished to pay severance pay, long service awards, and replacement rights. This study shows that legal protection for workers in employment termination disputes is not only determined by the litigation mechanism in the Industrial Relations Court, but also by the effectiveness of the implementation of workers' rights after the decision is rendered.